1994
DOI: 10.1161/01.cir.90.2.937
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of collateral blood flow in coarctation of the aorta by velocity encoded cine magnetic resonance imaging.

Abstract: This study shows the normal flow pattern in the descending thoracic aorta and its reversal in coarctation due to collateral flow. Thus, VENC-MR can measure collateral flow in coarctation and serves as a unique method for providing this important measurement of the severity of coarctation of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 26 publications
2
101
0
2
Order By: Relevance
“…Other groups have focused on the percent increase in descending aorta flow from collateral vessels to assess coarctation severity. 29 Steffens et al 30 reported that the percent increase in flow correlated with the diameter of the coarctation segment (rϭ0.94), with arm-toleg blood pressure difference (rϭ0.84), and with Doppler gradient (rϭ0.76). More recently, Araoz and colleagues 9 demonstrated that the percent increase in descending aorta flow in 19 patients with repaired CoA more accurately reflected the degree of narrowing than arm-to-leg blood pressure measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have focused on the percent increase in descending aorta flow from collateral vessels to assess coarctation severity. 29 Steffens et al 30 reported that the percent increase in flow correlated with the diameter of the coarctation segment (rϭ0.94), with arm-toleg blood pressure difference (rϭ0.84), and with Doppler gradient (rϭ0.76). More recently, Araoz and colleagues 9 demonstrated that the percent increase in descending aorta flow in 19 patients with repaired CoA more accurately reflected the degree of narrowing than arm-to-leg blood pressure measurements.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, with the development of contrast-enhanced MRA, this technique has replaced conventional angiography in the diagnosis of aortic coarctation. MR not only provides excellent morphologic images but also can be used to document hemodynamic significance (1,(3)(4)(5)(6). This approach for assessing coarctation severity is based upon measuring the flow in the distal aorta above the diaphragm and comparing it to the flow measured below the coarctation site (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…However, only recently has collateral flow been noninvasively quantified. Phase-contrast MR imaging (PC-MR) has been recognized to be a feasible method for assessing coarctation severity by quantifying collateral flow (1,(3)(4)(5)(6). This approach is based on measuring aortic flow in the distal aorta near the diaphragm and at a more proximal site just below the coarctation (5).…”
mentioning
confidence: 99%
“…Patients with less severe coarctation may not be diagnosed until later in childhood when a murmur is heard or hypertension noted. In these patients, collateral vessels develop from the internal thoracic and subclavian arteries, thyrocervical trunks, and vertebral and anterior spinal arteries to supply blood to the descending aorta [21,22] . For those who enter adulthood undiagnosed, hypertension is the most common presenting symptom [23] .…”
Section: Clinical Presentationmentioning
confidence: 99%